Exploring the therapeutic potential of the mitochondrial transfer-associated enzymatic machinery in brain degeneration - Luque-Campos, Noymar; Riquelme, Ricardo; Molina, Luis; Canedo-Marroquín, Gisela; Vega-Letter, Ana María; Luz-Crawford, Patricia; Bustamante-Barrientos, Felipe A. (Frontiers in Physiology, 2023)
Mitochondrial dysfunction is a central event in the pathogenesis of several degenerative brain disorders. It entails fission and fusion dynamics disruption, progressive decline in mitochondrial clearance, and uncontrolled oxidative stress. Many therapeutic strategies have been formulated to reverse these alterations, including replacing damaged mitochondria with healthy ones. Spontaneous mitochondrial transfer is a naturally occurring process with different biological functions. It comprises mitochondrial donation from one cell to another, carried out through different pathways, such as the formation and stabilization of tunneling nanotubules and Gap junctions and the release of extracellular vesicles with mitochondrial cargoes. Even though many aspects of regulating these mechanisms still need to be discovered, some key enzymatic regulators have been identified. This review summarizes the current knowledge on mitochondrial dysfunction in different neurodegenerative disorders. Besides, we analyzed the usage of mitochondrial transfer as an endogenous revitalization tool, emphasizing the enzyme regulators that govern this mechanism. Going deeper into this matter would be helpful to take advantage of the therapeutic potential of mitochondrial transfer.